Reterritorialization practices and strategies of campesinos in the urban frontier of Bogotá, Colombia - Quimbayo Ruiz, Germán A.; Kotilainen, Juha; Salo, Matti (Butterworth Scientific, 2020)
Much of the research on urbanization has focused on how rural populations move to cities for work opportunities. This paper takes a different perspective on the relations between rural populations and urbanization. The livelihoods of rural dwellers on the outskirts of the city of Bogotá in Colombia are increasingly affected by the expansion of urban activities and infrastructure. Therefore, urbanization takes place in the areas of residence of the rural populations; these people do not migrate to the city but, rather, the city migrates to them. Consequently, rural ways of life face growing competition from the production of commodities and services on the urban-rural fringe, including quarrying and landfills serving the needs of industries and urban populations. We explore how rural populations and their livelihoods have transformed as a response to these urban dynamics and the expansion of the city. We focus on the strategies that the rural populations employ to deal with the physical and socio-ecological impacts of this change. The defense of peri-urban livelihoods through these strategies is simultaneously social and spatial and has been partially successful. However, increasing social and environmental inequality, including worsening access to land, water and vital ecological functions, tends to lead to a general reduction in the quality of life in the urban frontier.
Keywords: Colombia; Latin America; Peri-urban farming; political ecology; Urbanization; urban design